Application of Mathematical Model for Raw Material Storage Management - C. Kasemset (2019)
© 2018 IEEE. This study proposed the mathematical model to obtain the appropriate storage methods for raw material at a case study company. Three classes of raw material as A, B, and C were stored using three types of storage equipment: pallet, shelf, and roller rack. The optimal solution showed that 94.60% of the storage area was used for current volume of raw material. After that, the amount of raw material was increased by 20% due to the expected customer demand. The optimal solution cannot be obtained because the storage area was not sufficient. The optimal solution indicated that the current storage area can handle up to 13.6% increment. Then, the sensitivity analyses were carried out. The results from the tests showed that to handle 20% increment as forecast, an additional storage area of increment 128.55 m 2 should be added to the current.